The impact of intensive sports training on the development of young girls - Pawluczyk, Maria; Zwoliński, Michał; Korpalski, Michał; Pawlikowski, Krzysztof; Żygłowicz, Marek; Torbicki, Adam; Augustyn, Dominik; Gaworek, Piotr; Marciniak, Mateusz; Trybuła, Alicja (Quality in Sport, 2025)
Introduction: Adolescence is a critical period for physical and mental development, during which physical activity can improve bone mineral density (BMD), reduce obesity, and enhance self-esteem. However, intense sports participation increases energy demands, potentially leading to energy deficits, particularly in female athletes. This energy imbalance can negatively impact the health of adolescent athletes. The purpose of research: This paper explores the effect of intensive training on the health of young female athletes. Material and methods: PubMed and Medline databases were searched. Relevant literature was selected. Results: A persistent state of low energy availability (LEA) has been demonstrated to lead to a variety of disorders, including menstrual irregularities, impaired bone microarchitecture, and depressive and anxiety symptoms. These abnormalities pose a particularly elevated risk to young female athletes, as they can result in severe lifelong complications. Conclusions: Every young female athlete should be screened for the symptoms of the syndrome of relative energy deficiency in sport (RED-S). Examination should be repeated at least annually. In the treatment of disorders arising from LEA, the primary objective is to enhance energy levels. In cases of low BMD, it is imperative to ensure an adequate supply of vitamin D and calcium in order to prevent fractures.